Reproductive strategies in loggerhead sea turtle Caretta caretta: polyandry and polygyny in a Southwest Atlantic rookery - Laís Amorim; Lara Chieza; Jake A. Lasala; Sarah de Souza Alves Teodoro; Wesley D. Colombo; Ana Carolina Barcelos; Paula Rodrigues Lopes Guimarães; João Luiz Guedes da Fonseca; Ana Claudia Jorge Marcondes; Alexsandro Santos; Sarah Vargas (PeerJ)
Sea turtles are highly migratory and predominantly inhabit oceanic environments, which poses significant challenges to the study of their life cycles. Research has traditionally focused on nesting females, utilizing nest counts and mark-recapture methods, while male behavior remains understudied. To address this gap, previous studies have analyzed the genotypes of females and hatchlings to indirectly infer male genotypes and evaluate the extent of multiple paternity within populations. Our research aimed to investigate the presence of multiple paternity in loggerhead turtle (Caretta caretta) nests for the first time in Brazil. We analyzed 534 hatchlings from 43 nests associated with 42 females during the 2017/18 to 2019/20 nesting seasons, using four highly polymorphic, species-specific microsatellite markers (nDNA). Parentage tests were conducted to reconstruct paternal genotypes and determine the rates of multiple paternity within clutches. Our results revealed that 72.09% of clutches were sired by multiple males, with contributions ranging from one to six males per clutch. Additionally, seven out of 88 males (7.95%) were found to have sired clutches from multiple females, with some males contributing to more than one clutch within and across breeding seasons. The breeding sex ratio (BSR) was calculated to be 2.09 males per female. While multiple paternity is a common phenomenon among sea turtles, this study is the first to document polyandry in loggerheads in Brazil and the first to provide evidence of polygyny in this species globally. This research establishes a crucial database for future studies in Brazil, with a focus on the BSR of the Southwest Atlantic subpopulation, offering essential insights for developing effective management strategies for this vulnerable population.